Analysis of Information Disclosure on Financial Assets According to PSAK 60 - Pratiwi, Fadilah; Dunakhir, Samirah; Idris, Hariany (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aimed: To find out whether PT Bank Mega Tbk in disclosing information on its financial assets complies with Statement of Financial Accounting Standards (PSAK) 60. The variable of this research is: disclosure of information on financial assets according to PSAK 60. The population of this study is the financial statements of PT Bank Mega Tbk, while the sample is the financial statements of PT Bank Mega Tbk 2022. Data collection was carried out using documentation study techniques and library research. Data analysis was performed with descriptive qualitative. The results of this study indicate that PT Bank Mega Tbk has not fully disclosed the disclosure of information on financial assets according to PSAK 60.